2022
DOI: 10.1590/s2175-97902022e20693
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of sunscreens and factors influencing sun protection: a review

Abstract: The effectiveness of sun protection depends directly on the photo-protective product employed, the way it is used and the amount applied. Many studies report that sunscreens are often applied incorrectly, at amounts much lower than those recommended for the sun protection factor (SPF) specified on the label. When not used properly, the effectiveness of the product against sun exposure damage is reduced. Currently, sunscreens are available in a variety of different formulations and types, such as stick (bar), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The UV protection efficacy of the EHMC-pEDGMA microgel was shown to be significantly superior to that of the original UVB absorbent EHMC. The determination of the sun protection factor is influenced by various factors, such as the methodology employed during experimentation, the formulation used, and the specific apparatus utilized for measurement [ 41 , 42 ]. The primary distinction observed in both the composition and functionality of the sunscreen recipe was the variation in the anti-UV ingredient utilized.…”
Section: Resultsmentioning
confidence: 99%
“…The UV protection efficacy of the EHMC-pEDGMA microgel was shown to be significantly superior to that of the original UVB absorbent EHMC. The determination of the sun protection factor is influenced by various factors, such as the methodology employed during experimentation, the formulation used, and the specific apparatus utilized for measurement [ 41 , 42 ]. The primary distinction observed in both the composition and functionality of the sunscreen recipe was the variation in the anti-UV ingredient utilized.…”
Section: Resultsmentioning
confidence: 99%
“…12 The data related to sunscreen SPF in this study is consistent with the current recommendation of using an SPF of 30 or more to provide the optimal protection which reflects good practice, Table 5. 16 Similarly, majority of sunscreen users (72%) in al Al-Robaee study used an SPF >30. 17…”
Section: Frequency and Percentage N (%)mentioning
confidence: 98%
“…The higher the SPF, the more protective the sunscreen [58] to prevent sunburn as well as skin cancer in the long term. The SPF can be determined with in vivo or in vitro methods.…”
Section: Uv-reduction and Sunscreenmentioning
confidence: 99%
“…Another study showed that the inhibition zone of catechin is 18.45 mm for P. acnes and 15.68 mm for S. epidermidis [60]. The antibacterial mechanism The higher the SPF, the more protective the sunscreen [58] to prevent sunburn as well as skin cancer in the long term. The SPF can be determined with in vivo or in vitro methods.…”
Section: Anti-acnementioning
confidence: 99%